Strategic Formulation of Islamic Boarding School-Based Educational Institutions to Improve Quality and Competitiveness - Indana, Nurul; Mutohar, Prim Masrokan; Akhyak, Akhyak; Zahiq, Moh. (PT. Riset Press International, 2025)
This study aims to formulate strategies for developing Islamic Boarding School-based educational institutions in order to improve quality and competitiveness. The analysis was conducted by identifying internal and external factors at MA Unggulan Darul Ulum STEP-2 IDB Jombang. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation, then analyzed using an interactive analysis model that included data collection, data reduction, data presentation, and conclusion drawing. The results of the internal factor analysis showed strengths in the form of good student characteristics, professional teachers and educational staff, adequate facilities and infrastructure, a Islamic Boarding School-based environment, and sufficient financial support. Meanwhile, several aspects were also weaknesses that needed to be improved. On the external side, opportunities were found in the form of extensive partnerships, public trust, and strategic location access, in addition to challenges in the form of competition between educational institutions. Based on this analysis, several development strategies were formulated, namely: curriculum development strategy; human resource development strategy; active, creative, innovative, and enjoyable learning strategy; facilities and infrastructure development strategy; student development strategy; strategy for strengthening the culture and environment of Islamic boarding schools; and strategy for strengthening management. This study confirms that the formulation of boarding school-based strategies can encourage improvements in the quality and competitiveness of Islamic educational institutions.